Barriers to vaccination against SARS-CoV-2 in Colombia: Narrative literature review - Bustillos-Serna, Carlos Felipe (2021)
Background: In December 2019, the SARS-CoV-2 virus started an outbreak of pneumonia in Wuhan, China, which spread rapidly around the world, making necessary the development of a vaccine for its containment. Colombia is one of the most affected countries in Latin America with a growing incidence and mortality, however, the country has launched the National Vaccination Plan in order to buy the necessary doses for herd immunity. Objective: To Identify the barriers encountered by the vaccine of SARS-CoV-2 in Colombia. Materials and methods: A systematic literature search was carried out as of April 9, 2021 in MEDLINE through PudMed, using the MeSh health descriptors “covid-19”, “SARS-CoV-2”, and “vaccine” combined with the Boolean connection “And” to identify publications that describe principles barred against vaccination. Results: Based on the PRISMA methodology, articles describing the barriers to vaccination of SARS-CoV-2 were identified, selected and included. Conclusion: It is converged that the main barrier that occurs in vaccination against SARS-CoV-2 in Colombia is vaccine hesitancy due to mistrust, which is caused by multiple sociocultural and socioeconomic factors.